Synthesis, Kinetic and Conformational Studies of 2-Substituted-5-(β-d-glucopyranosyl)-pyrimidin-4-ones as Potential Inhibitors of Glycogen Phosphorylase - Mavreas, Konstantinos F.; Neofytos, Dionysios D.; Chrysina, Evangelia D.; Venturini, Alessandro; Gimisis, Thanasis (Molecules, 2020)
Dysregulation of glycogen phosphorylase, an enzyme involved in glucose homeostasis, may lead to a number of pathological states such as type 2 diabetes and cancer, making it an important molecular target for the development of new forms of pharmaceutical intervention. Based on our previous work on the design and synthesis of 4-arylamino-1-(β-d-glucopyranosyl)pyrimidin-2-ones, which inhibit the activity of glycogen phosphorylase by binding at its catalytic site, we report herein a general synthesis of 2-substituted-5-(β-d-glucopyranosyl)pyrimidin-4-ones, a related class of metabolically stable, C-glucosyl-based, analogues. The synthetic development consists of a metallated heterocycle, produced from 5-bromo-2-methylthiouracil, in addition to protected d-gluconolactone, followed by organosilane reduction. The methylthio handle allowed derivatization through hydrolysis, ammonolysis and arylamine substitution, and the new compounds were found to be potent (μM) inhibitors of rabbit muscle glycogen phosphorylase. The results were interpreted with the help of density functional theory calculations and conformational analysis and were compared with previous findings.
Keywords: 5-; Cancer; catalytic site inhibitors; dft conformational analysis; glycogen phosphorylase; pyrimidin-4-one synthesis; Type 2 diabetes; β - d -glucopyranosyl